Coordination for market development - Poulton, Colin; Lyne, Michael C. (International Food Policy Research Institute, 2009)
One major body of literature in the application of institutional economics to market development concerns economic coordination. This literature seeks to explain why market systems are structured as they are, thereby revealing fundamental challenges that have to be addressed if efficient markets (for goods and services) are to develop. On a practical level, interest in coordination has risen dramatically as supply chains have become increasingly globalized and have tried to respond to the greater demands placed on them by consumers and regulators. In the agro-food sector, the dramatic rise in the power of supermarkets in many countries (Reardon et al. 2003) is associated with moves away from product sourcing through traditional wholesale markets toward vertically coordinated chains. It is in this context that Jaffee (1995, 25) writes: “In commodity systems analysis, the central focus is on the problems and mechanisms for coordination.”